Neraca Kefahaman Umat Islam Terhadap Hadith Rasulullah Saw Dan Penjelasannya - Amran Abdul Halim; Amiruddin Mohd Sobali; Abdulloh Salaeh; Ahmad Kamel Mohamed; Nidzamuddin Zakaria; Walid Mohd Said; Syed Najihuddin Syed Hassan; Mohammad Fahmi Abdul Hamid (Universiti Sains Islam Malaysia, 2024)
Papers In MALAY Language Date: 9 September 2021 Platform: MSTeams, USIM Nilai, Negeri Sembilan, Malaysia.